Advanced nursing recovery therapy in the field of nanotechnology based on tetracycline hydrochloride type drugs. (30th September 2020) - Li, Min; Ma, Yan; Yang, Lei; Li, Yulian
With the development of wound care theory and practice methods, the development of new materials and the improvement of sustained release and controlled release technologies, medical dressings will develop in the direction of multi-functionality, diversification and intelligence. This has also promoted the development of clinical care, better service for wound patients, new dressings, and new methods for wound care. Among many new dressings, nanotechnology-based polymer nanogels have good application prospects due to their good water retention properties and micelle stability properties. At present, a large number of researchers have developed a variety of wound care materials, which are widely used in clinical settings. However, due to the shape of the material or its characteristics, the mechanism of action of many materials has not been studied in detail. How to prepare a new type of wound dressing, which has multiple functions - integrating haemostasis, bacteriostatic, stimulating cell division and differentiation, accelerating tissue healing, moisturising and phlegm, etc., so as to achieve a good evaluation of patients' post-care recovery is. China's long-standing and urgent problem in the medical device market. Therefore, this study used the tetracycline hydrochloride drug doxycycline as an antibiotic drug for nano-modified dressings. Under the theoretical guidance of the interaction between wound healing and pH of microenvironment, a polyethylene glycol (PEG) modified PEG-doxycycline hydrogel nanocomposite dressing was prepared to study the stability of nanoparticles in the dressing. Physical and pH responsiveness, swelling behaviour of composite dressings, and physicochemical properties of drug release behaviour were studied. At the same time, in order to study the effect of the PEG-doxycycline nanocomposite hydrogel on the recovery of wound care in patients, this study applied the composite nano dressing to the clinic. Through the comparative study of patients' quality of life, wound healing, nursing satisfaction and treatment effect, the innovative application of tetracycline hydrochloride in the recovery of wound care of patients under nanotechnology is realised. The results of this study indicate that PEG-doxycycline nanocomposite hydrogel prepared under the guidance of nanotechnology can promote wound healing, shorten hospital stay and reduce complications. At the same time, the use of the dressing can also reduce the work of nursing, alleviate the suffering of the patient, improve the comfort of the patient, and greatly improve the nursing effect and effect on the patient. This has certain promotion and research value for the implementation of continuous nursing methods for patients with chronic wounds, which can be popularised in clinical practice.